Tingkat Partisipasi Pelaku Usaha dan Strategi dalam Pengurangan Penggunaan Kantong Belanja Plastik di Pasar Rakyat Kota Jambi dengan Menggunakan Analisis SWOT - Ilham Lahia; Anis Tatik Maryani; Muhammad Safri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Plastic waste is the number 1 contributor to waste in Jambi City based on data from SIPSN KHLK, 2021. This study aims to describe the level of participation of business actors, and the SWOT strategy for reducing the use of plastic shopping bags in the people's market in Jambi City. This study used two types of respondents, namely 7 experts and 93 public respondents with a questionnaire as a data collection instrument.The results of this study are: 1. The total value of the participation rate of business actors in the policy of reducing the use of plastic bags in people's markets is 22. So with a total score of 22, it can be classified into the category of low participation rate because it is between 0 to 33. Business actor participation is included in the Nonparticipation in the SWOT diagram it is included in quadrant I, which is a combination of strengths and opportunities (SO strategy) namely reducing the accumulation of plastic waste, creating business opportunities, changing people's habits in shop using environmentally friendly bags and make Jambi City a Pilot City for a City Without Plastic